A SYSTEMATIC ASSESSMENT FOR INVESTIGATING THE DESIGNED ATMOSPHERICS, ATTITUDE, BEHAVIOURAL IMPACT AND ITS RELATIONSIHPS IN RETAIL ENVIRONMENT. (WITH RESPECT TO RELIANCE TRENDS, BANGALORE) - SRINIVASA KRISHNA, Dr. KUCHI; RAO. VALLURI, Mr. VENKATA (The journal of contemporary issues in business and government, 2022)
Consumer shopping experience depends on their mood which could be impacting on all decisions that they take to the situations influence their current choices, particularly in the retail industry. India has occupied the fifth-largest global destination in retails space. The research investigates that how atmospherics, behavior and attitude are impacting the sales of a retail outlet with reference to visual merchandising. To know which factor has influenced the most in the sales and to know which factor has loaded more. The factors we took in the study are store display, window display, color and lighting, behavior, attitude, and purchase intention/sales. Henceforth the researcher made a modest effort to find the impact of Atmospherics, Attitude, Behavioural Impact and Its Relationships in Retail Environment